Implementasi Nilai Kelembagaan dan Kurikulum Madrasah Nizhamiyah dalam Reformasi Madrasah Kontemporer: Studi Kualitatif di Indonesia - Arif, Fadli Maulana; Iswantir, Iswantir (Lembaga Yasin AlSys, 2025)
Although madrasah reform has received attention in various previous studies, research that specifically examines the implementation of institutional values and the curriculum of Madrasah Nizhamiyah in contemporary madrasah contexts remains limited. This study aimed to explore the experiences of Islamic Religious Education (PAI) teachers in applying institutional values and Nizhamiyah curriculum principles in contemporary Indonesian madrasahs. A qualitative approach with a phenomenological case study design was employed, involving 14 PAI teachers selected through purposive sampling. Data were collected through in-depth interviews, classroom observations, and curriculum documentation, and were subsequently analyzed using thematic analysis to identify key themes and implementation patterns. The findings indicate that institutional values serve as the primary foundation of teaching practice, shaping students’ discipline, integrity, and collective responsibility. The integration of religious and general curricula is carried out holistically, although variations in implementation emerge due to differences in teacher creativity and limitations in formal guidelines. The principles of Madrasah Nizhamiyah are applied implicitly through the teacher’s role as a scholarly and moral figure, a character mentor, and a developer of students’ intellectual competencies. These findings contribute to the development of contemporary Islamic education theory and broaden understanding of the implementation of institutional values and Nizhamiyah principles in modern madrasah practice. The study concludes that the internalization of institutional values and the strengthening of the teacher’s role as a scholarly–moral figure are crucial for the success of madrasah reform, with theoretical implications for enriching the literature on contemporary Islamic education and practical implications for madrasahs and policymakers to reinforce operational guidelines, teacher training, and curriculum integration, while also opening avenues for further exploration of the application of Nizhamiyah principles in cross-disciplinary and long-term learning.